Analytical performance of the Lumipulse® G β‐Amyloid 1‐40 Plasma and Lumipulse® G β‐Amyloid 1‐42 Plasma RUO assays. (20th December 2022) - Vandijck, Manu; Degrieck, Rosina; Denoyette, Mario; Delanote, Jarne; De Jonge, Maarten; De Decker, Bart; Bastard, Nathalie Le; Vandenbroucke, Ina
Abstract: Background: Current research indicates that plasma β‐amyloid1‐42 /β‐amyloid1‐40 ratio has the potential for application in clinical settings and clinical trials to predict brain β‐amyloid burden. It could reduce the number of lumbar punctures (for CSF biomarker testing) or Aβ‐PET scans in light of clinical trial recruitment and could serve as a tool to evaluate target engagement and efficacy of disease‐modifying drugs. The aim of the current study was to demonstrate the analytical performance of the newly developed Lumipulse G β‐Amyloid 1‐40 Plasma and Lumipulse G β‐Amyloid 1‐42 Plasma RUO assays. Method: The LUMIPULSE G system is a chemiluminescent enzyme immunoassay platform enabling fully automated processing of samples using ready‐to‐use immunoreaction cartridges. Time to result in these single use test cartridges takes about 30 minutes. The analytical performance of the newly developed Lumipulse G β‐Amyloid 1‐40 Plasma and Lumipulse G β‐Amyloid 1‐42 Plasma RUO assays (using respectively 2G3 and 21F12 antibody for capturing and 3D6 antibody ALP‐conjugate for detection; two‐step immunoassay method) was determined. Parameters analysed were precision, sensitivity, linearity, and potential impact of interfering substances. The studies included a series of buffer‐ and K2 EDTA plasma‐based samples at different concentration levels, each tested in several replicates (70 µL/replicate (Aβ1‐40 ); 110 µL/replicate (Aβ1‐42 )) sized to the different parameters tested. Result: The total within‐lab variability of both assays was ≤6 % CV confirming high precision of the LUMIPULSE G system. Using low β‐amyloid concentrated plasma samples, the observed LoD was 0.44 pg/mL (Aβ1‐40 ) and 0.37 pg/mL (Aβ1‐42 ), and the LoQ was 0.44 pg/mL (Aβ1‐40 ) and 0.43 pg/mL (Aβ1‐42 ). Linearity was shown across the assay range (0 – 5000 pg/mL (Aβ1‐40 ); 0 – 1000 pg/mL (Aβ1‐42 )). No significant impact of commonly tested endogenous substances (bilirubin, chyle, triglycerides, rheumatoid factor (RF) and human anti‐mouse antibodies (HAMA)) was observed, except for haemoglobin. Conclusion: The analytical performance studies demonstrate – amongst other characteristics – low variability and high sensitivity enabling measurement of Aβ1‐40 and Aβ1‐42 in plasma. The Lumipulse G β‐Amyloid 1‐40 Plasma and Lumipulse G β‐Amyloid 1‐42 Plasma RUO assays are now ready to be explored further for clinical utility in various contexts of use.